Skill shortages and industrial clusters–empirical evidence from German establishment data - Tobias König; Thomas Brenner (The Annals of Regional Science, 2025)
Regional and sectoral skill shortages have attracted considerable attention in recent research on regional economics and economic geography. These shortages are a reality for many firms and organizations, with adverse consequences for individuals, firms, and the economy as a whole. Yet, it remains unclear whether skill shortages are more severe in industrial clusters due to intensified competition and labor poaching, or whether they are less severe because of labor pooling. This study examines the relationship between skill shortages and industrial clustering in Germany. Using generalized linear mixed regression models, the analysis draws on the IAB Establishment Panel dataset to assess the extent of shortages among clustered firms. The findings indicate that firms located in industrial clusters face a significantly lower probability of skill shortages, measured in terms of unfilled vacancies for skilled jobs. At the same time, however, clustered firms experiencing shortages encounter greater difficulties in filling these vacancies.
Keywords: J23; J63; R10; 500